Immunosuppressive activity of angiogenin in comparison with bovine seminal ribonuclease and pancreatic ribonuclease - Matousek, J; Soucek, J; Ríha, J; Zankel, T R; Benner, S A (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 1995)
Angiogenin, a member of the pancreatic-like ribonuclease family with a special biological action (RISBAses), is a basic protein that induces blood vessel formation. Another member of these special ribonucleases, bovine seminal ribonuclease (BS RNase), displays biological properties, including aspermatogenic, embryotoxic, antitumor and immunosuppressive activities. The effects of two angiogenin preparations tested on the biological activities mentioned above are reported and compared with those of BS RNase and RNase A. In contrast to RNase A, which was ineffective in all biological activities tested, angiogenin suppressed significantly the proliferation of human lymphocytes stimulated by phytohemagglutinin or concanavalin A or by allogenic human lymphocytes (mixed lymphocyte culture). However, angiogenin did not affect the growth of human tumor cell lines, development of cow and mouse embryos and spermatogenicity in mice. On the basis of these results, angiogenin is the first monomeric ribonuclease described so far that displays immunosuppressive activity similar to that of the dimeric BS RNase. The immunosuppressive activity of angiogenin might synergize with the effect on neovascularization of tumor tissues and thus contribute to the development of tumor.
Keywords: embryonální a fetální vývoj; Cell Division; Ribonuclease, Pancreatic; Pregnancy; Humans; Spermatogenesis; Tumor Cells, Cultured; proteiny; Endoribonucleases; pankreatická ribonukleasa; Proteins; Female; lidé; zvířata; myši; Lymphocyte Activation; imunosupresiva; Mice; nádorové buňky kultivované; Immunosuppressive Agents; aktivace lymfocytů; Cattle; ženské pohlaví; Male; spermatogeneze; těhotenství; skot; Embryonic and Fetal Development; Animals; mužské pohlaví; endoribonukleasy; buněčné dělení